KEGIATAN EKSTRA KURIKULER DAN PEMBENTUKAN SOFT SKILL PESERTA DIDIK DI SMA - Erine Nurmaulidya; Sudjarwo Sudjarwo; Pargito Pargito (Faculty of Teacher Training and Education, University of Lampung, 2013)
The objective of this research is to find out intended to study and assess the theoretically and empirical information that can be used to develop Soft Skills education through extra-curricular activities and view daily life Senior High School 6 the students in Bandar Lampung, and specifically the study aimed to determine the the pattern of extra-curricular activities and the formation of Soft Skills among one extra-curricular activities by conducting interviews with respondents informant teachers, stakeholders, parents and students and the research was conducted using qualitative descriptive approach. Data collection methods used were interviews, observation and documentation. The results of this thesis is known Soft Skill education through extra-curricular activities in SMA 6 Bandar Lampung has done well is seen during the observation I, II and III to the everyday student research note after note value attribute Extra-curricular Activities Soft Skill in establishing Learners Soft Skills in SMA 6 Bandar Lampung respondents ie Soft Skills attributes from entrenched is the willingness to learn, flexible, work in teams and logical argument. Pattern formation of Soft Skill training evaluation opinions of teachers, stakeholders, parents and learners after observing extra-curricular activities can be seen between the pattern formation of extra-curricular Soft Skills with each other no difference seen from the distribution of answers by respondent attribute values from entrenched Soft Skills (MM) of respondents answered extracurricular Osis and Rohis. Looks extra curricular emerging (MB) is an extra-curricular Arts Music. Starting to look (MT) Soft Skills attributes are in extra curricular sports and Paskibra.Keywords: soft skill, extra curriculer